The Non-Benzodiazepine Anxiolytic Drug Etifoxine Causes a Rapid, Receptor-Independent Stimulation of Neurosteroid Biosynthesis - do Rego, Jean Luc (PLoS One, 2015)
Neurosteroids can modulate the activity of the GABA(A) receptors, and thus affect anxiety-like behaviors. The non-benzodiazepine anxiolytic compound etifoxine has been shown to increase neurosteroid concentrations in brain tissue but the mode of action of etifoxine on neurosteroid formation has not yet been elucidated. In the present study, we have thus investigated the effect and the mechanism of action of etifoxine on neurosteroid biosynthesis using the frog hypothalamus as an experimental model. Exposure of frog hypothalamic explants to graded concentrations of etifoxine produced a dose-dependent increase in the biosynthesis of 17-hydroxypregnenolone, dehydroepiandrosterone, progesterone and tetrahydroprogesterone, associated with a decrease in the production of dihydroprogesterone. Time-course experiments revealed that a 15-min incubation of hypothalamic explants with etifoxine was sufficient to induce a robust increase in neurosteroid synthesis, suggesting that etifoxine activates steroidogenic enzymes at a post-translational level. Etifoxine-evoked neurosteroid biosynthesis was not affected by the central-type benzodiazepine (CBR) receptor antagonist flumazenil, the translocator protein (TSPO) antagonist PK11195 or the GABA(A) receptor antagonist bicuculline. In addition, the stimulatory effects of etifoxine and the triakontatetraneuropeptide TTN, a TSPO agonist, were additive, indicating that these two compounds act through distinct mechanisms. Etifoxine also induced a rapid stimulation of neurosteroid biosynthesis from frog hypothalamus homogenates, a preparation in which membrane receptor signalling is disrupted. In conclusion, the present study demonstrates that etifoxine stimulates neurosteroid production through a membrane receptor-independent mechanism.